Energy Audit of An Academic Institution (RIMT Polytechnic) - Kumar, Dharminder (My University, 2014)
An energy audit is a study of a plant or facility to determine how and where energy is used and to identify methods for energy savings. There is now a universal recognition of the fact that new technologies and much greater use of some that already exist provide the most hopeful prospects for the future. The opportunities lie in the use of existing renewable energy technologies, greater efforts at energy efficiency and the propagation of these technologies and options. Energy Auditing of academic building presented in this dissertation work takes into account the load data and electricity bills. Energy Audit in dissertation is focused on reduction in energy wastage and improvement power saving. Energy audit of RIMT polytechnic is done and various weak areas are identified on account of energy wastage. In this dissertation, multiple measures are suggested to college administration to reduce energy wastage .
M.E.(Power Systems& Drives)-Dissertation
Keywords: energy audit; energy conservation; energy audit; Energy management